The use of creative art as a strategy for case formulation in psychotherapy a case study - KARACA, SEMRA (My University, 2014)
Case formulation refers to the appraisal of the individual data and the treatment plan in terms of certain principles. In psychotherapy, case formulation is relevant for the recognition of conceptual and clinical tools as well as for the evaluation of the therapeutic endeavor. Artwork (painting) provides an effective tool for case formulation because it allows the individual to express his/her thoughts and emotions, which are prone to the influences of subconscious drives, conflicts, fears, and desires in a symbolic fashion. In this study, case formulation of a 31-year-old woman, who cannot overcome her verbal and physical aggressive behaviors, is presented. For case formulation, four sessions of artwork are used. The main purpose of the present case is to discuss the use of creative artwork as a means for case formulation in dynamic psychotherapy
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)